Red blood cell eNOS is cardioprotective in acute myocardial infarction - Miriam M. Cortese-Krott; Tatsiana Suvorava; Francesca Leo; Sophia K. Heuser; Anthea LoBue; Junjie Li; Stefanie Becher; Rebekka Schneckmann; Tanu Srivrastava; Ralf Erkens; Georg Wolff; Joachim P. Schmitt; et al. (Redox Biology, 2022)
Red blood cells (RBCs) were shown to transport and release nitric oxide (NO) bioactivity and carry an endothelial NO synthase (eNOS). However, the pathophysiological significance of RBC eNOS for cardioprotection in vivo is unknown. Here we aimed to analyze the role of RBC eNOS in the regulation of coronary blood flow, cardiac performance, and acute myocardial infarction (AMI) in vivo. To specifically distinguish the role of RBC eNOS from the endothelial cell (EC) eNOS, we generated RBC- and EC-specific knock-out (KO) and knock-in (KI) mice by Cre-induced inactivation or reactivation of eNOS. We found that RBC eNOS KO mice had fully preserved coronary dilatory responses and LV function. Instead, EC eNOS KO mice had a decreased coronary flow response in isolated perfused hearts and an increased LV developed pressure in response to elevated arterial pressure, while stroke volume was preserved. Interestingly, RBC eNOS KO showed a significantly increased infarct size and aggravated LV dysfunction with decreased stroke volume and cardiac output. This is consistent with reduced NO bioavailability and oxygen delivery capacity in RBC eNOS KOs. Crucially, RBC eNOS KI mice had decreased infarct size and preserved LV function after AMI. In contrast, EC eNOS KO and EC eNOS KI had no differences in infarct size or LV dysfunction after AMI, as compared to the controls. These data demonstrate that EC eNOS controls coronary vasodilator function, but does not directly affect infarct size, while RBC eNOS limits infarct size in AMI. Therefore, RBC eNOS signaling may represent a novel target for interventions in ischemia/reperfusion after myocardial infarction.